MANUFACTURING OF HYBRIDOMAS-PRODUCERS OF MONOCLONAL ANTIBODIES TO BRUCELLOSIS AGENT ANTIGENS - G. V. Kuklina; G. D. Elagin; O. O. Fomenkov; D. V. Pechenkin; A. V. Eremkin; A. A. Kytmanov (Проблемы особо опасных инфекций, 2017)
Objective of study is to prepare hybridomas-producers of monoclonal antibodies to brucellosis agent antigens. Materials and methods. B. abortus, B. melitensis, B. suis strains from the State collection of microorganisms of the 48th Central Research Institute Affiliated Branch and BALB/c mice. Hybridization was performed as described by G.Kohler and C.Milstein in modification by Fazekas De St. and Scheidegger D. The study of specific activity of immune sera, hybridoma supernatants, ascites fluid, and monoclonal antibody preparations was performed using ELISA. Results and conclusions. Obtained and characterized have been hybridomas-producers of monoclonal antibodies to specific antigens of brucellosis agent. They are active and stable antibody producers in the repeated passaging both, in vitro and in vivo. Obtained have also been the ascites fluid and preparations of monoclonal antibodies of brucellosis agent. Carried out has been substantiated selection of antibodies which could provide for the most sensitive ELISA. It is established that the monoclonal antibodies produced by hybridomas 232B6H7, 232G12F7, 233B2C5 in combination with brucellosis rabbit immunoglobulins allow for the identification of microbial cells of type strains of various Brucella species in concentrations ranging from 0,25·106 mc·sm–3 up to 1,0·106 mc·sm–3 and gave negative results with cultures of heterologous microorganisms in the contents of 1,0·108 mc·sm–3. Hybridomas-producers of monoclonal antibodies are planned to be used for the construction and manufacturing of immunodetection test-systems.